Interpersonal conflict management styles among academic administrators at International Islamic Universitty Malaysia - Nazaralievich, Kadamov Safarali (Institute of Education, International Islamic University Malaysia, 2012)
The purpose of this study is to investigate interpersonal conflict management styles practiced by academic administrators at International Islamic University Malaysia. Six research questions guided the testing of the intervention on interpersonal conflict management styles among academic administrators at International Islamic University Malaysia, based on Rahim and Bonoma's theoretical model of “concern for self and concern for others” of five interpersonal conflict management styles i.e. integrating, obliging, compromising, avoiding and dominating. Conflicts exist among us in our day to day lives regardless of being outside or within the organization, however, the existence of conflict nowadays is no longer considered as a problem, but rather the way administrators deal with it becomes a crucial issue. Administrators spend most of their times in managing their interpersonal conflicts while they could spend these times on other beneficial organizational activities. In this instance, for better management and better performance conflict management skills are useful and very significant in order to function effectively at any level within the organization (İslamoğlu et al., 2008). A quantitative survey research method has been employed for this study in which the Rahim Organizational Conflict Inventory-II (ROCI-II) survey questionnaire was distributed to 152 academic administrators in seven kulliyahs at IIUM. The findings for descriptive analysis revealed that academic administrators predominantly practice integrating conflict management style in managing their interpersonal conflicts. Next was compromising style followed by obliging, avoiding and lastly, dominating style. The findings for T-test results revealed that there is no significant difference between male and female academic administrators in practicing five interpersonal conflict management styles. Tests using one way ANOVA on age, job position, academic status and work experience also revealed no significant differences among the five interpersonal conflict management styles practiced by academic administrators at IIUM. In the research findings, there were some implications for academic administrators to practice and some recommendations made for future research on conflict management and its styles at International Islamic University Malaysia and other universities.